Changes in perception of gender differences in university male students after a self-determination program - Smith Palacio, Eulisis; Bravo-Sánchez, Alfredo; Díaz Ureña, Germán; Fraile, Juan (Frontiers in Education, 2024)
The aim of this study is to explore the outcomes of an intervention program to promote prosocial behaviour, foster personal responsibility and overcome gender stereotypes in sports. This is a mixed (qualitative-quantitative) quasi-experimental study using a single group. The sample consisted of 72 male university students (21.9 ± 8.85 years) enrolled in Spanish university. The program is based on the Self-determination Theory and consisted of 26 sessions. A teaching guide for gender equality in physical education, the "It Grows" program. The results of the study indicate that, firstly, the program is effective in significantly raising scores for the variable Personal Responsibility, improving decisionmaking and commitment to one's own goals. Secondly, there was an increase in Prosocial Behaviour, indicating greater degrees of empathy. Third, processes of intrinsic motivation also improved, with significantly higher scores in Basic Psychological Needs. Fourth, there was a decrease in the prevalence of gender stereotypes and sexist attitudes. An analysis of the pre-intervention correlations between variables indicated a positive and significant correlation between Personal Responsibility and Basic Psychological Needs (p < .001; r=.700), and between Responsibility and Prosocial Behaviour (p < .001; r=.504). After the intervention program, a positive correlation was found between scores for Personal Responsibility and Basic Psychological Needs (p < .001; r=.839) and between Personal Responsibility and Prosocial Behaviour (p < .001; r=.624). After the intervention program a negative correlation was also found between scores for Personal Responsibility and Gender Stereotypes (p < .001; r=-.281).